A hybrid methodology based on engineering tools for process standardization in accounting - Benito Baene, Diana Carolina; Samacá Zamora, Juan Sebastián; Fuentes Rojas, Ever Ángel (Ingeniería Solidaria, 2019)
Introduction: This article is the final product for the investigation developed on the case study entitled “Standardization of the accounting process for the “Liga Colombiana Contra el Cáncer”. This was performed between 2017 and 2018 at the faculty of Engineering of the “Universidad Libre”, Bogotá, Colombia. Problem: Lack of methodologies based on engineering tools for the standardization of accounting processes or similar fields. Objective: Propose a methodology based on engineering tools for the standardization of accounting processes. Methodology: This proposal is based on different engineering tools coupling that allowed to establish the following steps: Characterization, modeling, documentation, time study, indicators and impact evaluation. Results: Hybrid methodology that allowed to standardize the Accounting process on “Liga Colombiana Contra el Cáncer”. Conclusion: Standardization and coupling of the accounting process to the “Liga Colombiana Contra el Cáncer” management system. Originality: This methodology is applicable to processes with variable characteristics that are not couplers to traditional standardization tools. Limitations: There currently exists very little literature and research related to standardization methodologies and engineering tools applied to accounting or similar processes.